Multilayer flexible packaging technology and applications for the food, personal care and over-the-counter pharmaceutical industries - Wagner, John R., Jr (William Andrew ; Elsevier Science [distributor], 2009)
A comprehensive and highly practical survey of the materials, hardware, processes and applications of flexible plastic films. Aimed at a wide audience of engineers, technicians, managers, purchasing agents and users, Multilayer Flexible Packaging provides a thorough introduction to the manufacturing and applications of flexible plastic films, covering: Materials Hardware and Processes Multilayer film designs and applications The materials coverage includes detailed sections on polyethylene, polypropylene and additives. The dies used to produce multilayer films are explored in the hardware section, and the process engineering of film manufacture explained, with a particular focus on meeting specifications and targets. The section includes unique coverage of the problematic area of bending technology, providing a unique explanation of the issues involved in the blending of viscoelastic non-Newtonian polymeric materials. About the author John R. Wagner, Jr. is President of Crescent Associates, Inc., a consulting firm that specializes in plastic films and flexible packaging. He graduated from the University of Notre Dame with a BS and MS in Chemical Engineering.